Well lets solve for both.
6 + 2 + 4x
Combine like terms.
8 + 4x
Now solve the other one.
6 - (2 - 4x)
Distribute.
6 - 2 + 4x
Combine like terms.
4 + 4x.
These equations are not equivalent because instead of adding two, like in the first one, the second problem is subtracting. So you get 8 + 4x and 4 + 4x. I hope this helps love! :)
Hello from MrBillDoesMath!
Answer: b = 4, h = 13
Discussion:
For a triangle with base b" and height "h, the area formula is
A= (1/2)bh.
In our case A = 26, h = 5b-7, so
26 = (1/2) b (5b-7). Multiply both sides by 2:
26*2 = b(5b-7) =>
52 = b(5b-7) =>
52 = 5b^2 - 7b => (subtract 52 from both sides)
5b^2 - 7b - 52 = 0. This factors as follows:
(b - 4) (5 b + 13) = 0 (use quadratic formula to find this)
so b = 4 and h = 5b -7 = 5*4 - 7 = 13
Thank you,
MrB
Answer:
see below
Step-by-step explanation:
The volume of a cylinder is given by
V = pi r^2 h
We can find the radius from the diameter
r = d/2 = 34/2 = 17
V = (3.14) (17)^2 * 27
V =24501.42 m^3
The surface of a cone is found by
SA = pi r^2 + pi r l where l is the slant height
We can find the radius from the diameter
r = 8/2 = 4
SA =(3.14) * 4^2 + 3.14 * 4*7
=50.24+87.92
138.16 in^2
The lateral surface area of a pyramid is found by taking the area of the sides
LSA = 4 * the area of a triangle
we multiply by 4 since there are 4 sides
= 4 * 1/2 b*h where b is the base of the triangle and h is the height of the triangle. (in this case it would be the slant height)
= 2 * 8 *22
=352 m^2
If r=-3, then it would be -3-12 which equals -15